Efektivitas Penggunaan Media Pembelajaran Interaktif Berbasis Multimedia dalam Meningkatkan Minat Belajar Matematika pada Siswa SD - Irma Maulidia; Ibnu Muthi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to examine the effectiveness of the use of interactive learning media in improving the quality of mathematics learning in elementary school students. The main problem in mathematics learning at the elementary school level is the low interest and understanding of students towards abstract mathematical concepts. For this reason, interactive media is expected to be an alternative that is able to present material in an interesting, concrete, and easy-to-understand way for students. The research method used is a literature study with a qualitative descriptive approach, which involves analysis of a number of reference sources such as scientific journals, books, and current research reports that discuss similar topics. The results of the study show that interactive media is able to attract students' attention through the presentation of visuals, audio, and interactive activities that are in accordance with the learning characteristics of elementary school-aged children. This media has also been shown to increase students' motivation and interest in learning, because learning becomes more enjoyable and not boring. In addition, students' understanding of mathematical concepts increases due to the presence of visual representations that help bridge abstract concepts with concrete experiences. However, the effectiveness of interactive media also depends on the readiness of the technological infrastructure in schools and the competence of teachers in managing and utilizing the media. Therefore, support in the form of training and provision of facilities and infrastructure is needed so that interactive media can be implemented optimally in the learning process.